Esensi Ilmu Pengetahuan Perspektif Al-Qur’an: Analisis Surah al-Mujadalah Ayat 11 dan Shad Ayat 29 - Nurdiyanto, Nurdinyanto; Tauviqillah, Ahmad; Hafidz, Hafidz; Karman, Karman (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
Islam teaches that the acquisition of knowledge boils down to the source of knowledge, namely the Qur'an. In it there is a view of science in terms of the origin of science, the subject and object of what is studied, the epistemology of science, the urgency of science with the divine tawhid system. So with regard to that, this study aims to analyze; (1) the concept of science from the perspective of the Qur'an surah Al-Mujadalah verse 11 and Shad verse 29. The research method used is qualitative based on library studies. Data collection techniques used are documentation studies using library data derived from Tafsir, journal articles, relevant books. While the data analysis technique used with descriptive analysis, then the analysis can be studied in depth. The results of the study explain that the essence of science in the Qur'an Al-Mujadalah verse 11 and the Qur'an Shad verse 29, with regard to three things, namely (1) The Search for Knowledge, where a knowledge seeker must have manners, prioritize ethics before knowledge, be serious in the learning process, establish good relations between fellow human beings. (2) the function of science, namely dhikr or remembering, fikir or thinking, and righteous deeds, (3) the application of science in all aspects of life, which aims to be spiritual and practical in everyday life.